It's Not the CSI Effect: Criminal Justice Students' Choice of Major and Career Goals - Collica-Cox, Kimberly (International journal of offender therapy and comparative criminology, 2019)
The media tends to influence public perceptions of the criminal justice system. The media's impact, known as the CSI Effect, is not well documented in criminal justice majors. The present study adds to a small body of literature regarding the impact of media on criminal justice students' decisions, and seeks to identify the factors that influence students' choices, regarding their major/career goals. Based on the results from surveys administered at an urban university in the United States, most criminal justice students reported that they were not influenced by the media, yet the vast majority believed this to be true of their fellow majors. These students chose criminal justice because they found the subject matter interesting and relevant to the real world, and they wanted to work in a field in which they could be a problem solver. Upon graduation, these students overwhelmingly reported an interest in pursuing a career in federal law enforcement. Unfortunately, corrections, a field dedicated to working with offenders, was the lowest preferred profession among criminal justice students.